If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(s + 1) = -3 Reorder the terms: 7(1 + s) = -3 (1 * 7 + s * 7) = -3 (7 + 7s) = -3 Solving 7 + 7s = -3 Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 7s = -3 + -7 Combine like terms: 7 + -7 = 0 0 + 7s = -3 + -7 7s = -3 + -7 Combine like terms: -3 + -7 = -10 7s = -10 Divide each side by '7'. s = -1.428571429 Simplifying s = -1.428571429
| 5/4*y=15/4 | | 203/0 | | 9/4*x=99 | | 3*x=cos(x) | | 3x=cosx | | A=9/4(h-72) | | 4x^2+16x=-31 | | x^3-5x^2=47 | | 4-(8+y+6)=4 | | 5n+2=9 | | logx1/9=2 | | (2x+4)2=-15 | | 100-3x=21x+2 | | 15m+8=20 | | 63n/7=5 | | x+Squr(X)-30=0 | | 5(5y+3)=4(3y-5) | | 3X+2Y-2X= | | Log^4(6-5x)=1 | | 46=46/5 | | 1/3/2 | | 4/5*x=16/25 | | 6/7*t=66 | | 6/7x6=66 | | 19=7+29x-16x^2 | | 16/18=n/3 | | 4/9=16/28 | | f(x)=-5x^2+3x+1 | | 1/2x4x-4 | | 100=5(d+7) | | x=(0)+6 | | (0)=x+6 |